A novel pathogenic variant of DNMT3A associated with craniosynostosis: a case report of Heyn–Sproul–Jackson syndrome - Kim, Ga Hye; Kim, Jaewon; Lee, Jaewoong; Jang, Dae-Hyun (Frontiers in Pediatrics, 2023)
Pathogenic variants of DNMT3A have been implicated in Tatton-Brown-Rahman syndrome, an overgrowth disorder with macrocephaly and intellectual disability. However, there are recent reports of variants in the same gene giving rise to an opposing clinical phenotype presenting with microcephaly, growth failure, and impaired development—named Heyn-Sproul-Jackson syndrome (HESJAS). Here, we present a case of HESJAS caused by a novel pathogenic variant of DNMT3A. A five-year-old girl presented with severe developmental delay. Perinatal and family history were non-contributory. Physical exam showed microcephaly and facial dysmorphic features, and neurodevelopmental assessments revealed profound global developmental delay. Brain magnetic resonance imaging findings were normal; however, brain 3D computed tomography revealed craniosynostosis. Next generation sequencing revealed a novel heterozygous variant in DNMT3A (NM_175629.2: c.1012_1014+3del). The patient’s parents did not carry the variant. In this report, a novel feature associated with HESJAS (craniosynostosis) is described, along with a more detailed account of clinical manifestations than those in the original report.